Readiness of Indonesian Language Teachers for Implementing The Independent Learning Curriculum in High Schools - Pramadhanti, Dhelinta Fitri; Gusty, Nency (Universitas Muhammadiyah Surakarta, 2023)
This study aims to describe the readiness of high school teachers to implement the Independent Learning Curriculum. This readiness includes the teacher's understanding of the curriculum and the ability to prepare the learning tools that are included in the learning module. facilities and infrastructure that also support the implementation of the Merdeka Learning curriculum. This type of research is descriptive with a survey approach. The subjects of this study were Indonesian language teachers at SMA Negeri 3 Surakarta. The data collection used questionnaires and interviews, which were then analyzed descriptively through categorization based on each characteristic. The results of the study show that Indonesian language teachers are ready to apply to the Free Learning Curriculum. This readiness can be seen in: (1) understanding of curriculum content (80.83%); (2) teacher readiness in lesson planning (80.17); (3) teacher readiness in implementing learning (74.43%); and (4) teacher's understanding of evaluation and learning completeness (68.75%); and (5) facilities and infrastructure that support the learning process (100%). To increase readiness to implement the Free Learning Curriculum, it is necessary to do more socialization and training in the preparation of learning modules.